Review: Medication Error in Prescribing and Dispensing Phases on Outpatient: Review: Medication error dalam fase peresepan dan dispensing pada Pasien Rawat Jalan - Anwar, Ismail; Sinala, Santi; Nurisyah, Nurisyah; Adhayanti, Ida; Dewi, Sisilia Teresia Rosmala (Universitas Tadulako, 2022)
Background: A medication error is defined as